1977
DOI: 10.1007/bf00441935
|View full text |Cite
|
Sign up to set email alerts
|

Cortisone cataract in children with nephrotic syndrome

Abstract: In a group of 16 children with idiopathic nephrotic syndrome treated with corticosteroids for longer than 12 months, 9 developed a posterior subcapsular cataract (PSC). No correlation between the frequency of PSC and the duration of treatment and the total dose of treatment with steroids was demonstrable. However, the patients with PSC had received considerably higher average daily doses than those without PSC. Two patients with normal ophthalmologic findings at the end of treatment showed PSC 6 and 9 months l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has not been demonstrated that early ophthalmologic examinations can significantly lower the risk of glaucoma and cataracts. Previous studies reported that 10-56 % of children with renal disease, and treated with steroids, developed cataracts [66][67][68][69][70][71][72][73]. With respect to glaucoma, some studies found no increase in intraocular pressure; [72,73] however, other studies reported an increase of intraocular pressure in 20 % of the patients [71,74].…”
Section: Explanationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been demonstrated that early ophthalmologic examinations can significantly lower the risk of glaucoma and cataracts. Previous studies reported that 10-56 % of children with renal disease, and treated with steroids, developed cataracts [66][67][68][69][70][71][72][73]. With respect to glaucoma, some studies found no increase in intraocular pressure; [72,73] however, other studies reported an increase of intraocular pressure in 20 % of the patients [71,74].…”
Section: Explanationmentioning
confidence: 99%
“…The onset rate of posterior subcapsular cataracts does not appear to have a significant association with dose volume or steroid therapy, [66][67][68][69] suggesting that steroid sensitivity may be responsible. [69] Kobayashi et al and Hayasaka et al [70,71] reported that dose volume and steroid therapy duration are both associated with the rate of formation of cataracts.…”
Section: Cataractsmentioning
confidence: 99%